HuMenSCs Initiate the Uterus Stromal Decidualization in Mouse - Han, Yibing; Li, Zhaoyi; Shi, Hongliu; Dong, Yang; Chan, Tai Ip; Xiao, Gang; Zhu, Yi Zhun (Current Stem Cell Research & Therapy, 2025)
IntroductionHuman menstrual blood stem cells (huMenSCs) appear to be pre-clinically safe but a controlled phase I clinical trial is required to determine safety for clinical applications.MethodsHuMenSCs established from healthy donors were free of bacteria, mycoplasma, chlamydia, and endotoxin. P3 (passage 3) huMenSCs expressed the mesenchymal stem cell markers. P6 huMenSCs were developmental multipotential and could translocated into the uterine subepithelial stroma after intrauterine transplantation. After 10 and 15 passages, the huMenSCs kept normal karyotypes.ResultsGene expression showed that compared with the human umbilical cords mesenchymal stem cells (huMSCs), the huMenSCs affected the stromal cells more effectively. The huMenSCs possibly enhanced the stromal cell multiplication and “decidualization” process initiated by Igfbp1.ConclusionExpression of Igfbp1, Atf3, Ptgs2, Hoxa10, Nr4a1, and Fox A2 were significantly increased in the stromal cells of the huMenSCs transplanted uterine.
Keywords: huMSCs